The Analysis of Moral Values Reflected by the Main Characters in “Eternals” Movie - Kadek Lia Sri Agustini; I.B. Gde Nova Winarta (Austronesian: Journal of Language Science & Literature, 2023)
Literature is an art in the form of writing, but over time, literary works develop and have various forms. Besides being entertaining, literature also contains information and moral values. This study addresses the analysis of moral values in movies. The data used is Eternals movie. Researchers used the content analysis method to analyze the data. The leading theory used to analyze moral values in Eternals movie is Linda and Eyre (1993). The results show that 33 data are categorized into some types they are seven moral values of Loyalty and Trustworthy, three moral values of Respect, eight moral values of love and affection, six moral values of unselfishness and sensitivity, five moral values of kindness and friendliness, and four moral value of justice and mercy. The most dominant moral value of giving is love and affection. In conclusion, movies are one of the literary works that are in great demand by people because they are displayed in the form of motion pictures, which makes them easy to understand and entertain. Students think that learning through film analysis is a fun, engaging, and effective learning method. Besides being entertaining, movies can also provide the audience with information and moral values ​​related to real life. With this information and moral values, it is hoped that the audience will learn and apply them in everyday life to improve their lives.